PROSEDUR PROSES LAYANAN INDUSTRI KEUANGAN MENGGUNAKAN MODEL IDEF0 - Riyanto, Agus; Sianturi, Gabriel (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
This research aims to provide an overview of the procedure of the financial comparison service process in the form of credit card comparisons and mortgage loan comparisons conducted digitally in Indonesia. This research used a qualitative method using the IDEF0 model. Current financial services have used digital technology. A large amount of financial services competition conducted by Fintech has been able to trim the existing process procedures. Credit card comparisons and mortgage loan comparisons can be done online. Innovations made by Fintech for financial services have cut downtime and a long process so far. The display of financial service process procedures in the IDEF0 model is expected to make it easier for consumers to understand the comparison process.